Simmel and his Lectures on Education in the Context of German Progressive Education - Gonon, Philipp (Simmel Studies, 2019)
Georg Simmel is not really known for his pedagogical writing. Indeed, it did not represent his main focus, which was located in philosophy and sociology. The formation of a specific pedagogical science on a university level with its status of being an independent discipline happened only in the beginning of the 20th century: exactly at the same time when Georg Simmel was giving his lectures on Schulpädagogik (Lectures on Pedagogy for Schools) for teachers at the University of Strasbourg. It was also the time when progressive education became an international movement, aiming at activity, creativity, child-centeredness and youth activities in communities and nature. This article sketches Simmel’s approach towards pedagogy in terms of disciplinary thinking as well as his understanding of how teachers should behave in schools. A further aspect is the potential of his thinking for a theory of education (Bildung).